Deities and Their Symbolic Representation in Traditional Igbo Community: A Case Study if Alaogbaga Deity in Chokoneze Mbaise - Madukasi Francis Chuks; Ahamba Lilian Nneka (Randwick International of Social Science Journal, 2020)
Alaogbaga was/is an arbitrator of justice and morality. This deity was revered and respected by the people unlike today where the deity is relegated to the background. This research work discusses deities and their symbolic representation in an Igbo community focusing on Alaogbaga deity in Chokoneze Ezinihitte Mbaise local government area. The data collected were analyzed using the area cultural approach. In the course of the study, the researcher found out that Christianity, modernization and globalization are the agents that contributed to the weakening of the cultural heritage of Chokoneze people and the destabilization liturgical worship of Alaogbaga. The assimilation of these agents brought about negligence and abuse of the deity by different cadre. The effect of this negligence led to the weakening of the cultural heritage and in consequence the weakening of the moral practices associated with the traditional norms. This research will be beneficial to different cadre and will help enlighten and awaken the minds of the people. The researcher recommends that the people should go back to their root and reconcile with the positive traditions and moral values of their forefathers to help reduce the increasing rate of immorality. The Christian community together with the traditionalist should try to incorporate the teaching of the positive traditions of the community in their different organizations. Cultural studies should be included in the educational curriculum at all levels. This will help awaken the interest of the youths towards their cultural heritage and in turn give them a sense of identity.